2010
DOI: 10.1007/s10493-010-9392-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transcripts encode glucose 6-phosphate dehydrogenase in the southern cattle tick, Rhipicephalus (Boophilus) microplus

Abstract: Glucose 6-phosphate dehydrogenase (G6PDH) is an enzyme that plays a critical role in the production of NADPH. Here we describe the identification of four transcripts (G6PDH-A, -B, -C, and -D) that putatively encode the enzyme in the southern cattle tick, Rhipicephalus (Boophilus) microplus. The genomic DNA that is spliced to produce G6PDH-A and -B is 8,600-9,000 bases in length and comprises 12 exons. Comparison of the R. microplus G6PDH gene structure with those available from insects and mammals revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
5
2
0
Order By: Relevance
“…Glucose 6-phosphate dehydrogenase (G6PDH) is a NADPH-producing enzyme that was of critical role in the oxidative stage of the pentose phosphate pathway [ 77 ]. A study on R. microplus G6PDH showed four transcripts differentially expressed in engorged and/or unfed adults in which G6PDH-D showed upregulation as the one found in this study [ 78 ]. The 6-phosphofructo-2-kinase/fructose 2, 6-bisphosphatase (PFK-2/FBase-2) is a bifunctional enzyme that catalyzes either the synthesis (PFK-2 activity) or the degradation (FBase-2 activity) of fructose-2, 6-bisphosphate [ 79 ].…”
Section: Resultssupporting
confidence: 70%
“…Glucose 6-phosphate dehydrogenase (G6PDH) is a NADPH-producing enzyme that was of critical role in the oxidative stage of the pentose phosphate pathway [ 77 ]. A study on R. microplus G6PDH showed four transcripts differentially expressed in engorged and/or unfed adults in which G6PDH-D showed upregulation as the one found in this study [ 78 ]. The 6-phosphofructo-2-kinase/fructose 2, 6-bisphosphatase (PFK-2/FBase-2) is a bifunctional enzyme that catalyzes either the synthesis (PFK-2 activity) or the degradation (FBase-2 activity) of fructose-2, 6-bisphosphate [ 79 ].…”
Section: Resultssupporting
confidence: 70%
“…Glucose 6-phosphate dehydrogenase is a NADPH-producing enzyme that was of critical role in the oxidative stage of the pentose phosphate pathway [76]. A study on Rhipicephalus microplus G6PDH showed four transcripts differentially expressed in engorged and/or unfed adults in which G6PDH-D showed up-regulation as the one found in this study [77]. In M tick group most of the unigenes related to carbohydrate as energy were not signi cantly up-regulated, while unigenes on chitin synthesis and binding were signi cantly up-regulated (Table 5).…”
Section: Differential Gene Expression Pro Lessupporting
confidence: 68%
“…Glucose 6-phosphate dehydrogenase is a NADPH-producing enzyme that was of critical role in the oxidative stage of the pentose phosphate pathway [77]. A study on Rhipicephalus microplus G6PDH showed four transcripts differentially expressed in engorged and/or unfed adults in which G6PDH-D showed up-regulation as the one found in this study [78]. The 6-phosphofructo-2kinase/fructose 2,6-bisphosphatase (PFK-2/ FBase-2) is a bifunctional enzyme that catalyzes either the synthesis (PFK-2 activity) or the degradation (FBase-2 activity) of fructose-2,6-bisphosphate [79].…”
Section: Differential Gene Expression Pro Lessupporting
confidence: 68%